A Code Completion Problem in C Programming Learning Assistant System - Sandi Kyaw, Htoo Htoo; Htet, Ei Ei; Funabiki, Nobuo; Kuribayashi, Minoru; Myint, Thandar; Tar, Phyu Phyu; Min, Nandar Win; Thant, Hnin Aye; Wai, Phyu Hnin (2021 9th International Conference on Information and Education Technology (ICIET), 2021)
C programming has been the fundamental subject to a lot of university students for studying programming languages, algorithms, and computer architecture. Currently, we are developing C programming learning assistant system (CPLAS) for its self-study by extending our works of JPLAS for Java programming. JPLAS provides the code completion problem (CCP) to offer practical programming exercises. A CCP instance asks the completion of the given source code by filling in the missing elements. The correctness of the answer is marked through string matching by comparing each answer statement with the correct one. In this paper, we present the CCP by extending our works of the element fill-in-blank problem (EFP) in CPLAS. For evaluations, we generated 10 CCP instances and assigned them to 54 undergraduate students in Myanmar and Japan. Their solution results show that the CCP instances are generally suitable for C programming study by novice students, but those on pointer need improvements for better solutions.